Effect of PFN addition on microstructure and piezoelectric properties of PZT58/42 ceramics. Issue 187 (12th February 2018) - Photankham, W.; Kongpimai, J.; Phewphong, S.; Wattanasarn, H.; Samapisut, S.; Namthaisong, A.
ABSTRACT: In this work, the study effect of (1-x)Pb(Zr0.58 Ti0.42 )O3 -xPb(Fe0.5 Nb-0.5 )O3 or (1-x)PZT-xPFN ceramics composition at x = 0, 10 and 30 mol% was prepared by two-step sintering method. The phase structure and microstructure were analyzed by x-ray diffraction technique (XRD) and scanning electron microscopy (SEM), respectively. The piezoelectric properties of compound were examined and discussed such as dielectric properties and P−E hysteresis loop. The phase structure of (1-x)PZT-xPFN ceramics exhibited the phase transition between rhombohedral, tetragonal ferroelectric and coexist of monadic/cubic and tetragonal structure for PFN content addition. The average grain size increased significantly from 2.53 ± 0.1 µm to 5.01 ± 0.1 µm, which the addition of PFN content has been found grain growth of the sintering ceramics. When increasing PFN content, the dielectric constant maximum temperature changes temperature range from 376 to 285°C. For the dielectric constant increasing obtains the increases PFN content. But the piezoelectric coefficient ( d 33 ) of these ceramics decreased from 75 to 68 pC/N. g 33, kp and ϵr increased with of PZT increasing PFN content, while d 33 maximum of PZN58/42 and minimum of 0.1PFN.